Análise de interferências em redes Wi-Fi domésticas: estudo para solução dos problemas. - SILVA, Alan Sérgio da; ROSSETO, Caio Augusto Barretti (275, 2023)
O presente trabalho aborda o crescimento das redes Wi-Fi impulsionado pelo uso de dispositivos móveis, destacando a problemática das interfe-rências de sinal que podem prejudicar o desempenho da rede. O objetivo do trabalho é apresentar alternativas e equipamentos para resolver es-sas interferências, indicar locais ideais para a instalação de roteadores, apontar erros comuns dos usuários e avaliar as melhores frequências de transmissão. Além disso, propõe a implementação de uma rede Mesh para manter o sinal estável em um mesmo ambiente. A justificativa do trabalho é contribuir com sugestões e boas práticas para o uso de servi-ços de rede, considerando as particularidades de cada situação, visando a satisfação dos usuários. O texto destaca que interferências podem ocorrer por obstáculos físicos ou outros equipamentos na mesma fre-quência, propondo soluções como a instalação estratégica de roteado-res, avaliação de frequências e implementação de rede Mesh. Ao final, busca-se oferecer informações relevantes para pessoas comuns e ges-tores que desejam melhorar a experiência dos usuários em suas redes Wi-Fi.

This work addresses the growth of WI-FI networks, driven by the use of mobile devices, and the problem of signal interference that can affect network performance. The work aims to present alternatives and equip-ment to solve these interferences, define ideal locations for router instal-lation, point out common errors of users in the use of devices and evalu-ate the best transmission frequencies, besides implementing a Mesh net-work to keep the signal stable in the same environment. The justification for this work is to contribute with suggestions and good practices for the use of network services, considering the particularities of each network presented, aiming at user satisfaction. The signal interference in WI-FI networks can occur due to physical obstacles or other equipment in the same frequency, causing congestion in the transmission band. To solve these problems, the work proposes alternatives such as the installation of routers in strategic locations, evaluation of the best transmission fre-quencies and implementation of a Mesh network. Finally, the work seeks to provide relevant information to common people and company manag-ers who seek to implement effective solutions in the use of their WI-FI networks, in order to improve the user experience and ensure satisfaction with the services provided. Keywords: Interference. Mesh network. Wi-fi. Frequencies
Analysis of interference in domestic Wi-Fi networks: study to solve problems.
Keywords: Redes de informação; Internet; Informação e Comunicação